Measuring market-based core inflation expectations - Asger Munch Grønlund; Kasper Jørgensen; Fabian Schupp (European Central Bank (ECB), 2024)
We build a novel term structure model for pricing synthetic euro area core inflation-linked swaps, a hypothetical swap contract indexed to core inflation. Our approach relies on a term structure model of traded headline inflation-linked swap rates, which we assume span core inflation. The model provides estimates of market-based expectations for core inflation, as well as core inflation risk premia, at daily frequency, whereas core inflation expectations from surveys or macroeconomic projections are typically only available monthly or quarterly. We find that core inflation-linked swap rates are generally less volatile than headline inflation-linked swap rates and that market participants expected core inflation to be substantially more persistent than headline inflation following the 2022 energy price spike. Using an event-study methodology, we also find that monetary policy shocks significantly lower core inflation expectations.
Keywords: E31; E44; E52; 330; Inflation-linked swaps; affine term structure model; inflation expectations